Retorika Afektif dalam Komunikasi Pemerintah Daerah: Analisis Wacana Kritis Norman Fairclough terhadap Leksikon “Cinta” pada Program Pemerintah Kabupaten Jember - Kartika Bina Kasih; Atiyatul Mawaddah (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2026)
This study examines the use of the lexicon “love” (cinta) in the communication of the Jember Regency Government as a form of affective rhetoric within digital communication spaces. This phenomenon is particularly interesting because the word “love” is not only used as an emotional marker, but also forms part of program naming strategies and the construction of regional governmental identity. The aim of this research is to analyze the construction of the lexicon “love,” the discursive practices underlying it, as well as the social meanings, ideologies, and power relations represented through government communication. This study employs a qualitative approach using Norman Fairclough’s Critical Discourse Analysis (CDA), which encompasses textual, discursive practice, and sociocultural dimensions, and is further strengthened by microstructural analysis including transitivity, modality, nominalization, actor structure, and representational strategies. The data were obtained from the official website of the Jember Regency Government during the period January–April 2026, which contains programs based on the lexicon “love,” such as Peta Cinta, Bus Si Cinta, Jahe Cinta, and Beasiswa Cinta Bergema. The findings show that the lexicon “love” functions as an affective rhetorical device that integrates various sectors of public policy into a single symbolic narrative. At the microstructural level, there is a dominance of government representation as the primary actor and a naturalization of affect within policy language. At the mesostructural level, the production and distribution of discourse centralized in the Communication and Information Office (Diskominfo) create a uniform and emotionally charged narrative. Meanwhile, at the macrostructural level, the use of the lexicon “love” operates within the context of the emotionalization of politics and affective governance practices related to post-electoral political legitimacy. This study concludes that the lexicon “love” has undergone institutionalization in local government communication and functions as a master signifier that constructs a governance identity based on affect, emotional closeness, and symbolic legitimacy.